2020
DOI: 10.1111/lam.13439
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous fungi with high paraquat‐degrading activity isolated from contaminated agricultural soils in northern Thailand

Abstract: The contamination of paraquat (1,1′‐dimethyl‐4,4′‐bipyridylium dichloride) herbicide from the farming area has become a public concern in many countries. This herbicide harms to human health and negatively effects the soil fertility. Several methods have been introduced for the remediation of paraquat. In this study, 20 isolates of the paraquat‐tolerant fungi were isolated from the contaminated soil samples in northern Thailand. We found that isolate PRPY‐2 and PFCM‐1 exhibited the highest degradation activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
(51 reference statements)
2
0
0
Order By: Relevance
“…It was found that A. pseudopiperis and A. pseudotubingensis could tolerate methomyl and propargite, respec-tively, in the field at recommended dosages. These findings are consistent with previous studies that demonstrated that some PSF species of the genera Aspergillus, Chaetomium, Clonostachys, Grifola, Minimedusa, Mucor, Penicillium, Phycomyces, Pochonia, Purpureocillium, Rhizopus, and Trichoderma could tolerate agrochemicals at various dosages depending on the species and strain [101][102][103][104][105][106]. Notably, Benito et al [107] found that A. flavus AFS 63 and A. parasiticus APS 55 were able to tolerate glyphosate (herbicide) at the recommended field dosages.…”
Section: Discussionsupporting
confidence: 92%
“…It was found that A. pseudopiperis and A. pseudotubingensis could tolerate methomyl and propargite, respec-tively, in the field at recommended dosages. These findings are consistent with previous studies that demonstrated that some PSF species of the genera Aspergillus, Chaetomium, Clonostachys, Grifola, Minimedusa, Mucor, Penicillium, Phycomyces, Pochonia, Purpureocillium, Rhizopus, and Trichoderma could tolerate agrochemicals at various dosages depending on the species and strain [101][102][103][104][105][106]. Notably, Benito et al [107] found that A. flavus AFS 63 and A. parasiticus APS 55 were able to tolerate glyphosate (herbicide) at the recommended field dosages.…”
Section: Discussionsupporting
confidence: 92%
“…The data obtained indicates that concentration above 276 mg/L was toxic to these bacterial strains, leading to proportional decrease in biodegradation efficiency of paraquat. Research by Wongputtisin et al, (28), reported the optimum substrate to be 0.5g/L with a similar findings reported also by (27,29). This observation reinforces the notion that elevated paraquat concentrations could exert a toxic effect on metabolic activities, thereby potentially compromising the efficiency of bacterial degradation.…”
Section: Effect Of Substrate Concentration On Paraquatsupporting
confidence: 79%